Effects of Perinuclear Chromosome Tethers in the Telomeric URA3/5FOA System Reflect Changes to Gene Silencing and not Nucleotide Metabolism - Poon, Betty P.; Mekhail, Karim (Frontiers in Genetics, 2012)
Telomeres are repetitive DNA sequences that protect the ends of linear chromosomes. Telomeres also recruit histone deacetylase complexes that can then spread along chromosome arms and repress the expression of subtelomeric genes in a process known as telomere position effect (TPE). In the budding yeast Saccharomyces cerevisiae, association of telomeres with the nuclear envelope is thought to promote TPE by increasing the local concentration of histone deacetylase complexes at chromosome ends. Importantly, our understanding of TPE stems primarily from studies that employed marker genes inserted within yeast subtelomeres. In particular, the prototrophic marker URA3 is commonly used to assay TPE by negative selection on media supplemented with 5-fluoro-orotic acid (5FOA). Recent findings suggested that decreased growth on 5FOA-containing media may not always indicate increased expression of a telomeric URA3 reporter, but can rather reflect an increase in ribonucleotide reductase (RNR) function and nucleotide metabolism. Thus, we set out to test if the 5FOA sensitivity of subtelomeric URA3-harbouring cells in which we deleted various factors implicated in perinuclear telomere tethering reflects changes to TPE and/or RNR. We report that RNR inhibition restores 5FOA resistance to cells lacking RNR regulatory factors but not any of the major telomere tethering and silencing factors, including Sir2, Cohibin, Mps3, Heh1, and Esc1. In addition, we find that the disruption of tethering pathways in which these factors participate increases the level of URA3 transcripts originating from the telomeric reporter gene and abrogates silencing of subtelomeric HIS3 reporter genes without altering RNR gene expression. Thus, increased 5FOA sensitivity of telomeric URA3-harbouring cells deficient in telomere tethers reflects the dysregulation of TPE but not RNR. This is key to understanding relationships between telomere positioning, chromatin silencing, and lifespan.